The literacy of music from the traditional musics of chirimía caucana (Mayéutica Revista Científica de Humanidades y Artes, 2022)
Bachelor of Music students at the University of Cauca acquire pedagogical musical tools of European active methods for their professional practice, and although these provide important tools to future teachers, they lack contextualization. This research was developed to solve this problem, investigating the possibility of conceiving a contextualized method of musical literacy, taking advantage of the instrumental format and the musics of the Cauca shawms, as a complementary tool for the pedagogical and teaching practices of the students. The research method was based on ethnomusicology, with an epistemological approach to the constructivist paradigm (Valles Martínez, 1999). It was concluded that the elaboration of the method is a necessity because there are no methods of this nature in the Cauca context; The use of traditional music and the instrumental format of the Cauca shawms contributes to recovering, conserving, valuing and spreading traditional music to the new generations, increasing their sense of belonging.
Keywords: chirimía caucana; method of musical literacy; traditional music; elements of music